Application of Traditional Japanese Drug Jidabokuippo in a Modern Society - Nakae, Hajime; Irie, Yasuhito; Kitamura, Toshiharu; Okuyama, Manabu (Frontiers in Pharmacology, 2022)
Background: Jidabokuippo (JDI) has been used in Japan for alleviating contusion-induced swelling and pain since medieval Japan. Method: We summarize the benefits of applying JDI to various inflammations including bruises in a modern society. Results: Shuan Kagawa developed JDI and Sohaku Asada named it. JDI has not only been used to resolve blood[TM-1] stasis, but to also regulate qi in trauma patients. JDI is also applied to inflammatory swelling and pain caused by rheumatoid arthritis and cellulitis. Since the adverse event rate associated with JDI use was low (1.3%), JDI is considered a safe drug. Conclusion: JDI can be used for trauma patients mainly to resolve blood[TM-1] stasis even when adverse events of nonsteroidal anti-inflammatory drugs are concerned.